Self-Efficacy in Prevention of COVID-19 in Teenagers through Islamic-Based Animation Videos - Angga Wilandika; Fatiah Handayani; Suzana Yusof (UIN Sunan Gunung Djati Bandung, 2022)
Implementation of health protocols in preventing the transmission of COVID-19 infection in adolescents is still lacking. Although teenagers' knowledge regarding the implementation of health protocols is adequate, the attitude of teenagers, sometimes indifferent and less concerned, causes this health protocol not to be implemented. The way to handle this problem is by increasing self-efficacy for implementing the COVID-19 prevention protocol. The study aims to identify the impact of health education through Islamic-based COVID-19 prevention animation videos on teenagers' self-efficacy. This study was using a one-group pretest-post-test in the research design. The sampling technique used purposive sampling as many as 47 teenagers participated in this study. The teenager in this study is an individual who active in activities in the mosque environment. The intervention carried out in this study was health education through an Islamic-based animated video on COVID-19 prevention. Teenager self-efficacy measurements were measured using the 22-items Self-Efficacy Questionnaire for Implementing the COVID-19 Prevention Protocol. The paired t-test examines the difference between self-efficacy scores before and after health education. Significant differences were found in self-efficacy in implementing COVID-19 prevention protocols after health education (t = -2.596; p-value = 0.013). The present study suggests that health education using Islamic-based animated videos increases self-efficacy in teenagers. Therefore, health education through animated videos could improve teenagers' self-efficacy in efforts to implement COVID-19 prevention protocols, especially in mosque environments.